The Effectiveness of STAD Type Cooperative Learning Model on Students' Physics Comprehension Ability On Global Warming - Budyanti, Heny Yulia; Fairusy Fitria Haryani; Sukarmin (Department of Physics Education, Universitas Mataram, 2025)
This research aims to determine the effectiveness of using the STAD (Student Teams Achievement Division) cooperative learning model on global warming. This type of research is pre-experimental research using a one-group pretest-posttest design. The population of this research is class X students of SMA Negeri 7 Surakarta for the 2023/2024 academic year with a sample of class by cluster random sampling. Data collection techniques using multiple choice test to measure students' learning outcomes in understanding physics which were analyzed through normality test followed by an effectiveness test using the N–gain test. The research results show that the STAD (Student Teams Achievement Divisions) cooperative learning model influences students' understanding of physics on global warming. There is an increase in the average post-test score of 70.56 from the average pre-test score of 54.72 and the N-Gain value of 0.410 which is included in the medium category. Thus, the STAD cooperative learning model effectively enhance student achievement.